2009
DOI: 10.7202/029923ar
|View full text |Cite
|
Sign up to set email alerts
|

Les jeunes qui abandonnent les études secondaires ou collégiales : rapport à l’école et aux programmes d’aide à l’insertion socioprofessionnelle

Abstract: Cet article prend appui sur les résultats d’une recherche rétrospective menée auprès de 98 jeunes sortis sans diplôme de leur programme d’études à l’école secondaire et au cégep en 1996-1997. Il analyse 1) la perception que ces jeunes ont de leur décision d’abandonner les études et 2) leur recours aux programmes d’aide à l’insertion ainsi que leur rapport à la pratique d’intervention. L’article montre que la source de l’abandon des études et de l’inefficacité relative des programmes d’aide à l’insertion se tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Moreover, no control group was used in this study (that is, one group having undergone a communitybased intervention and the other not) in order to evaluate the real impact of the BO2 program and provide a comparison over time (before and after) (Duncan & Magnuson, 2003). Also, it was impracticable to take into account the characteristics of the young people (e.g., mental health problems) and their surroundings although it is recognized that students' networks (family, friends, and others), the mobilization of school teams, and a positive relationship between young people and the institutional system contribute significantly to preventing school drop-out (Beaumont, Bourdon, Couture, & Fortin, 2009;Vultur, 2009;Cook, 2008;Marcotte, Royer, Fortin, Potvin, & Leclerc, 2001;Rousseau, Tétreault, Bergeron, & Carignan, 2007;Molgat, 2007;Bourdon & Vultur, 2007). Another limitation concerns the impossibility of generalizing the results due to the small number of cases studied.…”
Section: Data Collectionmentioning
confidence: 99%
“…Moreover, no control group was used in this study (that is, one group having undergone a communitybased intervention and the other not) in order to evaluate the real impact of the BO2 program and provide a comparison over time (before and after) (Duncan & Magnuson, 2003). Also, it was impracticable to take into account the characteristics of the young people (e.g., mental health problems) and their surroundings although it is recognized that students' networks (family, friends, and others), the mobilization of school teams, and a positive relationship between young people and the institutional system contribute significantly to preventing school drop-out (Beaumont, Bourdon, Couture, & Fortin, 2009;Vultur, 2009;Cook, 2008;Marcotte, Royer, Fortin, Potvin, & Leclerc, 2001;Rousseau, Tétreault, Bergeron, & Carignan, 2007;Molgat, 2007;Bourdon & Vultur, 2007). Another limitation concerns the impossibility of generalizing the results due to the small number of cases studied.…”
Section: Data Collectionmentioning
confidence: 99%
“…The professional integration of underqualified youth is a global challenge (Michaud et al 1997;Jellab 2005;Smith 2012;Cahuc et al, 2013). Vultur (2009) demonstrated that youth without a diploma or recognized qualifications are more likely to have precarious work, be less well paid, and experience mediocre working conditions. Professional training in the workplace can alleviate some of these difficulties (Mlynaryk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…L'absence de diplomation résultant de l'abandon scolaire est un problème préoccupant pour plusieurs pays industrialisés (d 'Ortun, 2009), et ce, d'autant plus que les jeunes sans diplôme ou qualification reconnue courent davantage de risques d'exercer des emplois précaires, moins bien rémunérés et aux conditions de travail médiocres (Lemire, 2010;Vultur, 2009). Les jeunes Québécois n'échappent pas à cette réalité.…”
Section: Introductionunclassified